2014
DOI: 10.5539/ass.v10n11p132
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Behavior Cyberbullying in Thailand: Incidence and Predictors of Victimization and Cyber-Victimization

Abstract: Cyberbullying is becoming an important issue internationally, including in Thailand. I report findings from a questionnaire survey of 1,183 students drawn from 12 schools in southern Thailand, aged 14 to 17 years. The questions asked included demographic information, use of ICT, as well as experiences of being a victim or perpetrator of traditional bullying (not cyber) and cyberbullying. Students were asked if they had been bullied (not cyber), or cyberbullied at school in the past couple of months. We used tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…These results echo those studies using similar time periods and adolescent samples. For instance, Sittichai ( 2014 ) found that 6% of 14–17-year-old students were bullied frequently over the past couple of months. In another study, 7.1% of 10–13-year-old students were bullied online frequently in the last 3 months (Price et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results echo those studies using similar time periods and adolescent samples. For instance, Sittichai ( 2014 ) found that 6% of 14–17-year-old students were bullied frequently over the past couple of months. In another study, 7.1% of 10–13-year-old students were bullied online frequently in the last 3 months (Price et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This initial sample of 1,200 fell to 1,183 who responded; this was the sample used in Sittichai (2014), who reported on prevalence data, and risk factors for being a victim. However after excluding participants with missing data in coping strategies, this fell to a final total of 1,049 adolescents used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Two small-scale studies have been reported on coping with cyberbullying. Sittichai and Tudkea (2015) reported qualitative research on cyberbullying behaviors, using semi-structured interviews with twenty seven victims and perpetrators. For coping with cyberbullying, some kept quiet, deleted or blocked others, responded or cyberbullied back, compromised, or stopped or cancelled access to social networking.…”
Section: Studies On Bullying and Cyberbullying In Thailandmentioning
confidence: 99%
“…Strategies depend on the age of the cybervictim. Moreover, school programs containing strategies in preventing cyberbullying situations such as: "whole-school" anti-bullying policy, awareness-raising program, and curriculumbased activities should be implemented (Sittichai, 2014).…”
Section: People: International Journal Of Social Sciences Issn 2454-5899mentioning
confidence: 99%